2015
DOI: 10.1039/c4py01662a
|View full text |Cite
|
Sign up to set email alerts
|

Dual role for alkali metal cations in enhancing the low-temperature radical polymerization of N,N-dimethylacrylamide

Abstract: The radical polymerization of N,N-dimethylacrylamide (DMAAm) has been investigated in the presence of several alkali metal salts, including lithium bis(trifluoromethanesulfonyl)imide (LiNTf 2 ). The addition of an alkali metal salt led to a significant increase in the yield and molecular weight of the resulting polymer.NMR analysis of mixtures of DMAAm and LiNTf 2 suggested that DMAAm was being activated by the coordination of Li + to its CvO group. Electron spin resonance analysis of the DMAAm polymerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 71 publications
5
36
0
Order By: Relevance
“…53,54 Indeed, in spectroscopic investigations of vinyl monomers and Li 1 salts, cation complexation has been detected using IR as well as 1 H and 13 C NMR spectroscopy. 55,56,[58][59][60] Based on similar evidence, it can be confirmed that these species are also formed in our study. As displayed in Figure 9, the C@O stretching peaks of MMA undergo shifts to lower wavenumbers following the addition of LiTf 2 N at monomer:salt ratios of 1:1 and 2:1.…”
Section: -68supporting
confidence: 91%
See 2 more Smart Citations
“…53,54 Indeed, in spectroscopic investigations of vinyl monomers and Li 1 salts, cation complexation has been detected using IR as well as 1 H and 13 C NMR spectroscopy. 55,56,[58][59][60] Based on similar evidence, it can be confirmed that these species are also formed in our study. As displayed in Figure 9, the C@O stretching peaks of MMA undergo shifts to lower wavenumbers following the addition of LiTf 2 N at monomer:salt ratios of 1:1 and 2:1.…”
Section: -68supporting
confidence: 91%
“…56,58,59 The mechanism of the reduction in the rate of termination in these reactions has been assigned to a variety of factors including radical stabilization and single electron-alkali metal interactions as well as electrostatic repulsion between complexed macroradicals. 56,58,59,62 The improvements in the reaction kinetics of the polar vinyl monomers in this study may be due, in part, to these effects. We attribute improvements in overall monomer conversions to structuring of the monomers about the Li 1 cation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][29][30][31][32][33][34][35][36][37][38][39][40][41] Recently, we have also found that inclusion of alkali metal bis(trifluoromethanesulfonyl)imides (MNTf 2 ), such as LiNTf 2 , in the radical polymerization of N,Ndimethylacrylamide (DMAAm) leads to a significant increase in the yield and molecular weight of the resulting polymer. 42 NMR analysis of a mixture of DMAAm and LiNTf 2 suggests that DMAAm is activated by the coordination of Li + to its CvO group. Furthermore, electron spin resonance (ESR) spectroscopic analysis of the polymerization in the presence of LiNTf 2 suggests that the propagating radical is stabilized by Li + , probably through a single-electron lithium bonding, which is a recently proposed theory.…”
Section: Introductionmentioning
confidence: 99%
“…152 More recently, Hirano and coworkers examined the use of high concentrations of alkali metal triflates and triflimides (MNTf 2 ), finding that the relatively weak LA, NaNTf 2 , in a 1:1 ratio with monomer increased isotactic content to m ¼ 85% in DMA polymerizations. 153 While this example of isotactic control is intriguing, it is probably more readily attributed to electrostatic repulsion between the side-chains rather than a chelation mechanism.…”
Section: Lewis Acids In Radical-based Polymer Synthesismentioning
confidence: 97%